Prevalence of ocular pseudoexfoliation in type II diabetes mellitus - Bahnam Yousif, Afrah; Abdulgani, Ahmed (Zanco Journal of Medical Sciences (ZJMS), 2024)
Background and objective: Pseudoexfoliation syndrome is a systemic disorder related to age mostly affects the anterior structures of the eye. It is characterized by increased production and accumulation of abnormal fibrillar material inextraocular and intraocular tissues. There was a variation in the prevalence of pseudoexfoliation syndrome in diabetic patients compared with non-diabetic patients. The aim of the study is to estimate the prevalence of pseudoexfoliation syndrome among diabetic patients in a sample of the Iraqi population and evaluate the impacting factor that affects this prevalence Methods: A cross-sectional study was conducted in the Ophthalmology Department/ Erbil Teaching Hospital during the period from 1st of August 2021 to 31st of March 2022. A convenient sample of 100 patients with an age of ≥50 years old and who were diagnosed with type 2 diabetes were enrolled in the current study. The questionnaire included sociodemographic characteristics of the patients (age, gender, smoking, and alcohol state), past medical history and investigations (duration of diabetes mellitus and HbA1c), and the results of the ophthalmologic history and examination including intraocular pressure, presence of diabetic retinopathy, and the presence of pseudoexfoliation syndrome Results: About 52% of the patients were aged 50-59 years, while 9% had an age of ≥70 years. The prevalence of pseudoexfoliation syndrome was 9%. While diabetic retinopathy was presented in 37%. The prevalence of glaucoma was 12%. There was a significant association between pseudoexfoliation syndrome incidence and increasing the age of the patients, the highest prevalence was among patients with ≥70 years (P = 0.001). The pseudoexfoliation syndrome was significantly associated with diabetic retinopathy, the presence of glaucoma, and diabetic duration (P-values were 0.001, 0.001, and 0.026, respectively). In addition, the mean intraocular pressure was significantly higher among those with pseudoexfoliation syndrome than patients without pseudoexfoliation syndrome (P = 0.001) Conclusion: The prevalence of pseudoexfoliation syndrome in diabetic patients was 9%. The duration of diabetes, diabetic retinopathy, glaucoma, and the age of the participants significantly impacted the prevalence of pseudoexfoliation syndrome.